Self-Cleaning and Antibacterial Zeolitic Imidazolate Framework Coatings - Miao, W.; Wang, J.; Liu, Jian; Zhang, Y. (Wiley-VCH Verlag, 2018)
© 2018 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim Superhydrophobic surface with self-cleaning function like lotus leaf can inhibit bacterial adhesion to some extent; however, it cannot completely avoid bacterial contamination because it could not kill them. In this work, a facile modified sol–gel method to prepare self-cleaning and antibacterial coating is proposed. Zeolitic imidazolate framework-8 (ZIF-8) nanoparticles with good hydrophobic and antibacterial properties are mixed with polyvinylidene fluoride (PVDF) colloidal particle suspension, then, the PVDF/ZIF-8 nanocomposite is modified with 1H, 1H, 2H, 2H-perfluorooctyltriethoxysilane (POTS) to prepare PVDF/ZIF-8/POTS (PZP) coating solution. The resultant PZP nanocomposite coatings have a high contact angle (>160°) and a low sliding angle (<7°). Meanwhile, it is found that the dirt particles accumulated on the surface can be easily washed off by rolling water droplets, demonstrating its superb self-cleaning function. Notably, the PZP nanocomposite coating shows excellent antibacterial activity against Gram-negative Escherichia coli. These ZIF-8-based nanocomposite coatings with superb self-cleaning function and high antibacterial activity denote their great potential in a wider range of practical applications.